Wear and biomechanical characteristics of a novel shear-reducing insole with implications for high-risk persons with diabetes - Constantinides, Georgios; Lavery, Lawrence A.; Lanctot, Dan R.; Zamorano, Ruben G.; Athanasiou, Kyriacos A.; Agrawal, Mauli Mauli (My University, 2005)
Objective: This study was designed to measure pressure and shear reduction of a novel insole design. Methods: We compared three multilayer viscoelastic insoles to a novel insole design (GlideSoft®, Xilas Medical, Inc., San Antonio, TX). The bottom pad of each insole was fabricated from firm-density Plastazote® [Apex Foot Products (now Aetrex), South Hackensack, NJ] with an upper of Plastazote, ethyl vinyl acetate, or PORON® (Langer Biomechanics Group, Inc., Deer Park, NY). The GlideSoft design used the same materials with two intervening thin sheets of a low friction material. We measured foot pressures, shear, and material stiffness prospectively as the insoles aged during daily usage in 30 healthy adults. We used the F-Scan® (Tekscan, Inc., Boston, MA) to determine in-shoe foot pressures and the Automated Stress-relaxation Creep Indenter System (Xilas Medical) to measure material stiffness. To evaluate shear force, the insole was placed on the slide assembly of a custom-designed shear tester equipped with a reciprocating mechanism and force transducers. Results: The GlideSoft exhibited 57% less peak shear force than the standard insole (P < 0.05) in laboratory testing under simulated conditions. Ethyl vinyl acetate had higher compressive stiffness values than Plastazote and PORON at all test intervals (P < 0.05). There were no statistical differences between any of the insoles for peak in-shoe pressure measurements (P > 0.05). Conclusions: The GlideSoft design demonstrated a significant reduction in shear while maintaining equivalent pressure reduction compared with standard insole designs with three different material combinations for up to 320,000 steps.
Keywords: Polyethylene; Vinyl acetate; Biomechanics; Viscoelasticity